Sodium ion button half cell and preparation method thereof
By preparing the long-handled almond shell into a hard carbon material and assembling it into a sodium ion buckle half-cell, the problem of insufficient performance of the negative electrode material of the sodium ion battery is solved, and a high capacity and high efficiency sodium ion battery is achieved, which is suitable for commercial applications.
Patent Information
- Application Number
- CN202411342893.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2024-12-31
AI Technical Summary
The development of negative electrode materials of existing sodium ion batteries is lagging behind, especially in commercial applications, with poor rate performance and reversible capacity, which limits the widespread application of sodium ion button batteries.
The long-handled almond shell is used as the carbon precursor, and the long-handled almond shell is prepared by cleaning, crushing, decomposition, freeze-drying and pyrolysis, and assembled into a sodium ion buckle half-cell as a negative electrode material. Accelerated sodium ion desolvation treatment is carried out to improve the reversible capacity of the battery and the first week of Coulomb efficiency.
It achieves a high-capacity sodium storage platform and excellent chemical stability, improves the reversible capacity of sodium ion batteries and the first-week Coulomb efficiency, simplifies the preparation process, and is suitable for large-scale production.
Smart Images

Figure CN119230958A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sodium ion batteries, and in particular relates to a sodium ion button-type half-cell. The present invention also relates to a method for preparing the battery. Background Art
[0002] Lithium-ion batteries have been widely used in energy storage systems due to their high power density and long cycle life. They dominate the fields of electric vehicles and portable electronic products. However, the uneven distribution and scarcity of lithium resources limit the application of lithium-ion batteries in large-scale power storage. At present, most lithium resources are heavily dependent on imports, which greatly limits the further development of lithium-ion batteries. Therefore, the development of new batteries is of great significance to promoting my country's green and low-carbon development. Sodium and lithium are elements of the same main group, with similar physical and chemical properties, wide distribution, abundant reserves, and low prices. Sodium-ion batteries have advantages such as lower cost and higher safety than lithium-ion batteries. They are expected to replace lithium-ion batteries in many fields such as new energy vehicles and energy storage grids. They are a promising battery technology and have received widespread attention from researchers. At present, researchers have developed many sodium-ion battery positive electrode materials, but the development of a negative electrode material suitable for the practical application of sodium-ion batteries still faces many challenges.
[0003] Carbon-based materials are considered one of the most promising negative electrode materials due to their considerable ion storage capacity, good conductivity and excellent thermochemical stability. Soft carbon and hard carbon are the two most common amorphous carbon-based materials on the market. Among them, hard carbon materials are considered to be more ideal negative electrode materials for sodium ion batteries due to their low cost, non-toxicity, environmental protection and low sodium storage potential. The sources of hard carbon material precursors are mainly divided into biomass-based, polymer-based and coal-based carbon materials. Biomass materials stand out among many materials due to their abundance, low cost, sustainability and economic advantages. They are the first choice for commercial negative electrode materials. However, poor rate performance and low reversible capacity are still a major challenge for their commercial application.
[0004] At the same time, most existing research focuses only on electrode materials, while only a handful of studies have been conducted on sodium-ion batteries as a whole. Sodium-ion button batteries are a type of rechargeable battery similar to lithium-ion batteries, with advantages such as high energy density, high output power, and long life. Compared with lithium-ion batteries, sodium-ion batteries have advantages such as a wider range of raw material resources and lower costs, so they have attracted much attention. Summary of the invention
[0005] The object of the present invention is to provide a sodium ion button half-cell having the characteristics of high reversible capacity and high first-cycle coulombic efficiency.
[0006] Another object of the present invention is to provide a method for preparing the above-mentioned button-type half-cell.
[0007] The technical solution adopted by the present invention is a method for preparing a sodium ion button half-cell, which is specifically implemented according to the following steps:
[0008] S1, washing the long-pedunculate almond shell, drying it, crushing it and passing it through a 100-mesh sieve to obtain long-pedunculate almond shell powder;
[0009] S2, using excess hydrochloric acid to remove impurity ions in the long-handled almond shell powder obtained in step S1, filtering out the hydrochloric acid, and then washing and drying the powder;
[0010] S3, breaking the powder obtained in step S2 into cells, freezing it, and then freeze-drying it;
[0011] S4, carbonizing the powder obtained in step S3 under Ar atmosphere to obtain a long-handled almond shell-based hard carbon material;
[0012] S5, using the hard carbon material obtained in step S4 as a negative electrode material to prepare a negative electrode sheet;
[0013] S6, using the negative electrode sheet obtained in step S5 as the negative electrode, the sodium sheet as the positive electrode, and a glass fiber separator to assemble a sodium ion button half-cell;
[0014] S7, subjecting the button-type half-cell assembled in step S6 to a sodium ion accelerated desolvation treatment to obtain a sodium ion button-type half-cell.
[0015] The present invention is also characterized in that:
[0016] Step S2 is specifically as follows:
[0017] The long-handled almond shell powder obtained in step S1 is immersed in excess hydrochloric acid and stirred for 4 to 6 hours to remove impurity ions therein. After filtering out the hydrochloric acid, the powder is ultrasonically washed with deionized water, and then dried by air blast and then vacuum dried.
[0018] The specific drying process is: forced air drying at 60-80°C for 12-15h, and then vacuum drying at 90-100°C for 12-15h.
[0019] Step S3 is specifically as follows:
[0020] Add deionized water with a mass of 10 to 15 times the mass of the powder to the long-handled almond shell powder obtained in step S2, stir for 1 to 2 hours, then break the cells for 2 to 3 hours, freeze for 24 to 48 hours, and freeze-dry for 36 to 48 hours;
[0021] In step S4, the specific carbonization process is: heating to 1200-1600°C at a rate of 1-5°C / min and then keeping the temperature for 3 hours.
[0022] Step S5 is specifically as follows:
[0023] A conductive agent and a binder are added to the long-handled almond shell-based hard carbon material obtained in step S4 and mixed to obtain an active slurry, the active slurry is coated on a current collector, and vacuum dried at 60°C for 24 hours to obtain a negative electrode sheet; wherein the conductive agent is conductive carbon black, the binder is formed by dissolving polyvinylidene fluoride in N-methyl-2-pyrrolidone, the mass ratio of the long-handled almond shell-based hard carbon, the conductive carbon black and the polyvinylidene fluoride is 8:1:1, and the current collector is copper foil.
[0024] In step S7, the specific steps of the sodium ion accelerated desolvation treatment are: maintaining a constant temperature of 60-80° C. in a vacuum drying oven for 7-8 days.
[0025] Another technical solution adopted by the present invention is a sodium ion button half-cell, which is prepared by the above preparation method.
[0026] The beneficial effects of the present invention are:
[0027] (1) The negative electrode material of the battery of the present invention is made of long-handled almond shell, which has a wide source of raw materials, is green and environmentally friendly, and has low cost;
[0028] (2) The method of the present invention uses long-handled tonsil shell as a carbon precursor, and obtains a long-handled tonsil shell-based hard carbon material through washing, crushing, impurity removal, freeze drying and pyrolysis. The hard carbon material has a high-capacity sodium storage platform and excellent chemical stability, and is very suitable as a negative electrode material for sodium ion batteries;
[0029] (3) The method of the present invention uses a long-handled almond shell-based hard carbon material as a negative electrode material to prepare a negative electrode sheet, and a sodium sheet as a positive electrode sheet, to assemble a sodium ion button half-cell, and perform a sodium ion accelerated desolvation treatment, so that the obtained battery has a higher reversible capacity and first-cycle coulomb efficiency;
[0030] (4) The method of the present invention is simple and easy to operate, has strong repeatability, and can be scaled up for production, thus providing a feasible and effective method for the preparation of sodium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 is a scanning electron microscope image of the hard carbon material prepared in Example 1 of the present invention;
[0032] Figure 2 is an X-ray diffraction pattern of the hard carbon material prepared in Example 1 of the present invention;
[0033] Figure 3 is N of the hard carbon material prepared in Example 1 and Comparative Example 1 of the present invention. 2 Comparison of adsorption-desorption isotherms;
[0034] Figure 4 is a pore size distribution diagram of the hard carbon materials prepared in Example 1 of the present invention and Comparative Example 1;
[0035] Figure 5 is the SAXS spectrum and fitting result of the hard carbon material prepared in Example 1 of the present invention;
[0036] Figure 6 This is the first charge and discharge curve of the hard carbon material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0037] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0038] The method for preparing the sodium ion button half-cell of the present invention is specifically implemented according to the following steps:
[0039] S1, washing the long-pedunculate almond shell, drying it, crushing it and passing it through a 100-mesh sieve to obtain long-pedunculate almond shell powder;
[0040] S2, immersing the long-handled almond shell powder obtained in step S1 in excess hydrochloric acid, stirring for 4 to 6 hours to remove impurity ions therein, filtering out the hydrochloric acid, ultrasonically washing the powder with deionized water for 3 to 5 times, each time for 7 to 10 minutes, and then drying it with air at 60 to 80° C. for 12 to 15 hours, and then vacuum drying it at 90 to 100° C. for 12 to 15 hours;
[0041] S3, placing the long-handled almond shell powder obtained in step S2 in a beaker, adding deionized water with a mass of 10 to 15 times the mass of the powder, stirring for 1 to 2 hours, then breaking the cells for 2 to 3 hours, then freezing for 24 to 48 hours, and then freeze-drying for 36 to 48 hours;
[0042] S4, placing the powder obtained in step S3 in a tube furnace, heating to 1200-1600° C. at a rate of 1-5° C. / min under an Ar atmosphere, and then maintaining the temperature for 3 hours for carbonization to obtain a long-handled almond shell-based hard carbon material;
[0043] S5. Add a conductive agent and a binder to the long-handled almond shell-based hard carbon material obtained in step S4 and mix them to obtain an active slurry, apply the active slurry on a current collector, and vacuum dry at 60° C. for 24 hours to obtain a negative electrode sheet; wherein the conductive agent is conductive carbon black (Super-P), the binder is formed by dissolving polyvinylidene fluoride (PVDF) in N-methyl-2-pyrrolidone (NMP), the mass ratio of the long-handled almond shell-based hard carbon, the conductive carbon black and the polyvinylidene fluoride is 8:1:1, and the current collector is copper foil;
[0044] S6, using the negative electrode sheet obtained in step S5 as the negative electrode, the sodium sheet as the positive electrode, and a glass fiber separator to assemble a sodium ion button half-cell in an argon atmosphere in a glove box;
[0045] S7, subjecting the button-type half-cell assembled in step S6 to a sodium ion accelerated desolvation treatment, specifically, placing it in a vacuum drying oven at a constant temperature of 60-80° C. for 7-8 days to obtain a high-performance sodium ion button-type half-cell.
[0046] Example 1
[0047] The long-pedunculate almond shell was peeled from the long-pedunculate almond, washed with deionized water, and dried in a blast drying oven for 6 hours. The dried long-pedunculate almond shell was transferred to a grinder and crushed, and then sieved with a 100-mesh screen to obtain long-pedunculate almond shell powder. Weigh 5g of long-pedunculate almond shell powder and immerse it in 200mL of 5mol / L hydrochloric acid, stir for 4 hours to remove impurity ions, and then filter the hydrochloric acid. The long-pedunculate almond shell powder was ultrasonically washed with deionized water 4 times, 200mL of water each time, ultrasonic for 7 minutes, then transferred to a 60℃ blast oven to dry for 12 hours, and then vacuum dried at 90℃ for 12 hours to obtain the long-pedunculate almond shell powder after acid washing. Subsequently, take 2g of the obtained product and place it in a beaker and add 20mL of deionized water. After stirring with a magnetic bar for 1 hour, the cells were broken for 2 hours, transferred to a refrigerator for freezing for 24 hours, and then freeze-dried for 48 hours. Finally, the obtained product was placed in a porcelain boat and transferred to a tube furnace. The temperature was increased to 1400°C at a heating rate of 1°C / min under an argon atmosphere and kept for 3 hours to obtain a long-handled almond shell-based hard carbon material.
[0048] The long-handled almond shell-based hard carbon obtained above was ground and sieved with a 400-mesh screen as an active material. N-methyl-2-pyrrolidone was used as a solvent, and the hard carbon was mixed with conductive carbon black and polyvinylidene fluoride in a mass ratio of 8:1:1. After degassing in a degassing machine for 1 hour, the negative electrode slurry was obtained and coated on a copper foil with a scraper of a certain thickness. Bake in a vacuum drying oven for 12 hours, then take out and cut into negative electrode sheets with a diameter of 12 mm; assemble the sodium ion battery in a glove box, then place it in a vacuum drying oven at 60°C for 7 days, and finally conduct electrochemical performance tests.
[0049] Example 2
[0050] The long-pedunculate almond shell was peeled from the long-pedunculate almond, washed with deionized water, and dried in a blast drying oven for 6 hours. The dried long-pedunculate almond shell was transferred to a grinder and crushed, and then sieved with a 100-mesh screen to obtain long-pedunculate almond shell powder. Weigh 5g of long-pedunculate almond shell powder and immerse it in 200mL of 5mol / L hydrochloric acid, stir for 6 hours to remove impurity ions, and then filter the hydrochloric acid. The long-pedunculate almond shell powder was ultrasonically washed with deionized water 3 times, 300mL of water each time, ultrasonic for 10 minutes, then transferred to an 80℃ blast oven to dry for 12 hours, and then vacuum dried at 100℃ for 12 hours to obtain the long-pedunculate almond shell powder after acid washing. Subsequently, 2g of the obtained product was placed in a beaker and 30mL of deionized water was added. After stirring with a magnetic bar for 2 hours, the cells were broken for 2 hours, transferred to a refrigerator for freezing for 48 hours, and then freeze-dried for 36 hours. Finally, the obtained product was placed in a porcelain boat and transferred to a tube furnace. The temperature was increased to 1600°C at a heating rate of 5°C / min under an argon atmosphere and kept for 3 hours to obtain a long-handled almond shell-based hard carbon material.
[0051] The long-handled almond shell-based hard carbon obtained above was ground and sieved with a 400-mesh screen as an active material. N-methyl-2-pyrrolidone was used as a solvent, and the hard carbon was mixed with conductive carbon black and polyvinylidene fluoride in a mass ratio of 8:1:1. After degassing in a degassing machine for 1 hour, the negative electrode slurry was obtained and coated on a copper foil with a scraper of a certain thickness. Bake in a vacuum drying oven for 12 hours, then take out and cut into negative electrode sheets with a diameter of 12 mm; assemble the sodium ion battery in a glove box, then place it in a vacuum drying oven at 70°C for 7 days, and finally conduct electrochemical performance tests.
[0052] Example 3
[0053] The long-pedunculate almond shell was peeled from the long-pedunculate almond, washed with deionized water, and dried in a blast drying oven for 6 hours. The dried long-pedunculate almond shell was transferred to a grinder and crushed, and then sieved with a 100-mesh screen to obtain long-pedunculate almond shell powder. Weigh 5g of long-pedunculate almond shell powder and immerse it in 200mL of 5mol / L hydrochloric acid, stir for 5 hours to remove impurity ions, and then filter the hydrochloric acid. The long-pedunculate almond shell powder was ultrasonically washed with deionized water 5 times, 200mL of water each time, and ultrasonic for 8 minutes, then transferred to a 70℃ blast oven to dry for 15 hours, and then vacuum dried at 90℃ for 15 hours to obtain the long-pedunculate almond shell powder after acid washing. Subsequently, take 2g of the obtained product and place it in a beaker and add 25mL of deionized water. After stirring with a magnetic bar for 1 hour, the cells were broken for 3 hours, transferred to a refrigerator for freezing for 24 hours, and then freeze-dried for 48 hours. Finally, the obtained product was placed in a porcelain boat and transferred to a tube furnace. The temperature was increased to 1200°C at a heating rate of 3°C / min under an argon atmosphere and kept for 3 h to obtain a long-handled almond shell-based hard carbon material.
[0054] The long-handled almond shell-based hard carbon obtained above was ground and sieved with a 400-mesh screen as an active material. N-methyl-2-pyrrolidone was used as a solvent, and the hard carbon was mixed with conductive carbon black and polyvinylidene fluoride in a mass ratio of 8:1:1. After degassing in a degassing machine for 1 hour, the negative electrode slurry was obtained and coated on a copper foil with a scraper of a certain thickness. Bake in a vacuum drying oven for 12 hours, then take out and cut into negative electrode sheets with a diameter of 12 mm; assemble the sodium ion battery in a glove box, then place it in a vacuum drying oven at 60°C for 8 days, and finally conduct electrochemical performance tests.
[0055] Example 4
[0056] The long-pedunculate almond shell was peeled from the long-pedunculate almond, washed with deionized water, and dried in a blast drying oven for 6 hours. The dried long-pedunculate almond shell was transferred to a grinder and crushed, and then sieved with a 100-mesh screen to obtain long-pedunculate almond shell powder. Weigh 5g of long-pedunculate almond shell powder and immerse it in 200mL of 5mol / L hydrochloric acid, stir for 4 hours to remove impurity ions, and then filter the hydrochloric acid. The long-pedunculate almond shell powder was ultrasonically washed with deionized water 4 times, 200mL of water each time, ultrasonic for 10 minutes, then transferred to a 60℃ blast oven to dry for 14 hours, and then vacuum dried at 100℃ for 13 hours to obtain the long-pedunculate almond shell powder after acid washing. Subsequently, 2g of the obtained product was placed in a beaker and 20mL of deionized water was added. After stirring with a magnetic bar for 1 hour, the cells were broken for 2 hours, transferred to a refrigerator for freezing for 36 hours, and then freeze-dried for 48 hours. Finally, the obtained product was placed in a porcelain boat and transferred to a tube furnace. The temperature was increased to 1500°C at a heating rate of 1°C / min under an argon atmosphere and kept for 3 hours to obtain a long-handled almond shell-based hard carbon material.
[0057] The long-handled almond shell-based hard carbon obtained above was ground and sieved with a 400-mesh screen as an active material. N-methyl-2-pyrrolidone was used as a solvent, and the hard carbon was mixed with conductive carbon black and polyvinylidene fluoride in a mass ratio of 8:1:1. After degassing in a degassing machine for 1 hour, the negative electrode slurry was obtained and coated on a copper foil with a scraper of a certain thickness. Bake in a vacuum drying oven for 12 hours, then take out and cut into negative electrode sheets with a diameter of 12 mm; assemble the sodium ion battery in a glove box, then place it in a vacuum drying oven at 70°C for 7 days, and finally conduct electrochemical performance tests.
[0058] Example 5
[0059] The long-pedunculate almond shell was peeled from the long-pedunculate almond, washed with deionized water, and dried in a blast drying oven for 6 hours. The dried long-pedunculate almond shell was transferred to a grinder and crushed, and then sieved with a 100-mesh screen to obtain long-pedunculate almond shell powder. Weigh 5g of long-pedunculate almond shell powder and immerse it in 200mL of 5mol / L hydrochloric acid, stir for 5 hours to remove impurity ions, and then filter the hydrochloric acid. The long-pedunculate almond shell powder was ultrasonically washed with deionized water 5 times, 200mL of water each time, ultrasonic for 10 minutes, then transferred to an 80℃ blast oven to dry for 12 hours, and then vacuum dried at 90℃ for 12 hours to obtain the long-pedunculate almond shell powder after acid washing. Subsequently, take 2g of the obtained product and place it in a beaker and add 20mL of deionized water. After stirring with a magnetic bar for 1 hour, the cells were broken for 2 hours, transferred to a refrigerator for freezing for 24 hours, and then freeze-dried for 48 hours. Finally, the obtained product was placed in a porcelain boat and transferred to a tube furnace. The temperature was increased to 1300°C at a heating rate of 1°C / min under an argon atmosphere and kept for 3 hours to obtain a long-handled almond shell-based hard carbon material.
[0060] The long-handled almond shell-based hard carbon obtained above was ground and sieved with a 400-mesh screen as an active material. N-methyl-2-pyrrolidone was used as a solvent, and the hard carbon was mixed with conductive carbon black and polyvinylidene fluoride in a mass ratio of 8:1:1. After degassing in a degassing machine for 1 hour, the negative electrode slurry was obtained and coated on a copper foil with a scraper of a certain thickness. Bake in a vacuum drying oven for 12 hours, then take out and cut into negative electrode sheets with a diameter of 12 mm; assemble the sodium ion battery in a glove box, then place it in a vacuum drying oven at 60°C for 7 days, and finally conduct electrochemical performance tests.
[0061] Comparative Example 1
[0062] The method is basically the same as Example 1, except that freeze drying is not performed. The specific steps are as follows:
[0063] The long-handled almond shell was peeled from the long-handled almond, washed with deionized water, and dried in a blast drying oven for 6 hours. The dried long-handled almond shell was transferred to a grinder and crushed, and then sieved with a 100-mesh screen to obtain long-handled almond shell powder. 5g of long-handled almond shell powder was weighed and immersed in 200mL of 5mol / L hydrochloric acid, stirred for 4 hours to remove impurity ions, and then the hydrochloric acid was filtered. The long-handled almond shell powder was ultrasonically washed with deionized water 4 times, 200mL of water each time, and ultrasonic for 7 minutes, then transferred to a 60℃ blast oven for drying for 12 hours, and then vacuum dried at 90℃ for 12 hours to obtain the long-handled almond shell powder after acid washing. Finally, the obtained product was placed in a porcelain boat and transferred to a tube furnace, and heated to 1400℃ at a heating rate of 1℃ / min in an argon atmosphere, and kept warm for 3 hours to obtain a long-handled almond shell-based hard carbon material.
[0064] The long-handled almond shell-based hard carbon obtained above was ground and sieved with a 400-mesh screen as an active material. N-methyl-2-pyrrolidone was used as a solvent, and the hard carbon was mixed with conductive carbon black and polyvinylidene fluoride in a mass ratio of 8:1:1. After degassing in a degassing machine for 1 hour, the negative electrode slurry was obtained and coated on a copper foil with a scraper of a certain thickness. Bake in a vacuum drying oven for 12 hours, then take out and cut into negative electrode sheets with a diameter of 12 mm; assemble the sodium ion battery in a glove box, then place it in a vacuum drying oven at 60°C for 7 days, and finally conduct electrochemical performance tests.
[0065] Comparative Example 2
[0066] The method is basically the same as Example 1, except that the sodium ion accelerated desolvation treatment is not performed. The specific steps are:
[0067] The long-pedunculate almond shell was peeled from the long-pedunculate almond, washed with deionized water, and dried in a blast drying oven for 6 hours. The dried long-pedunculate almond shell was transferred to a grinder and crushed, and then sieved with a 100-mesh screen to obtain long-pedunculate almond shell powder. Weigh 5g of long-pedunculate almond shell powder and immerse it in 200mL of 5mol / L hydrochloric acid, stir for 4 hours to remove impurity ions, and then filter the hydrochloric acid. The long-pedunculate almond shell powder was ultrasonically washed with deionized water 4 times, 200mL of water each time, ultrasonic for 7 minutes, then transferred to a 60℃ blast oven to dry for 12 hours, and then vacuum dried at 90℃ for 12 hours to obtain the long-pedunculate almond shell powder after acid washing. Subsequently, take 2g of the obtained product and place it in a beaker and add 20mL of deionized water. After stirring with a magnetic bar for 1 hour, the cells were broken for 2 hours, transferred to a refrigerator for freezing for 24 hours, and then freeze-dried for 48 hours. Finally, the obtained product was placed in a porcelain boat and transferred to a tube furnace. The temperature was increased to 1400°C at a heating rate of 1°C / min under an argon atmosphere and kept for 3 hours to obtain a long-handled almond shell-based hard carbon material.
[0068] The long-handled almond shell-based hard carbon obtained above was ground and sieved with a 400-mesh screen as an active material. N-methyl-2-pyrrolidone was used as a solvent, and the hard carbon was mixed with conductive carbon black and polyvinylidene fluoride in a mass ratio of 8:1:1. After degassing in a degassing machine for 1 hour, the negative electrode slurry was obtained and coated on a copper foil with a scraper of a certain thickness. Bake in a vacuum drying oven for 12 hours, then take out and cut into negative electrode sheets with a diameter of 12 mm; assemble the sodium ion battery in a glove box, then place it in a vacuum drying oven at room temperature for 7 days, and finally conduct electrochemical performance tests.
[0069] The hard carbon materials and half-cells prepared in the examples and comparative examples were subjected to the following performance tests:
[0070] like Figure 1, which is a SEM image of the hard carbon material prepared in Example 1, it can be seen that the prepared hard carbon material has a certain pore structure and can be used to store sodium ions.
[0071] like Figure 2 As shown, it is the XRD spectrum of the hard carbon material prepared in Example 1. The characteristic peak of the C element can be clearly seen from the figure, wherein the (002) peak corresponds to the parallel stacking of graphene sheets inside the material. The sharper the peak, the higher the degree of graphitization of the material. It can be seen that the hard carbon material of the present invention has a broad peak and a low degree of graphitization; and the (100) peak is caused by the sp2 hybridized carbon inside the material, indicating that the long-handled almond shell-based hard carbon material exhibits an amorphous nature.
[0072] like Figure 3 As shown, N of the hard carbon material prepared in Example 1 and Comparative Example 1 2 From the comparison diagram of adsorption-desorption isotherm curves, it can be seen that the hard carbon material of comparative example 1 has not been freeze-dried, and the freeze-dried hard carbon material of embodiment 1 has a higher specific surface area, indicating that after freeze-drying, more pore structures are formed in the material, thereby increasing its specific surface area.
[0073] like Figure 4 As shown, it is the pore size distribution diagram of the hard carbon materials prepared in Example 1 and Comparative Example 1. It can be seen that the pore size of the hard carbon material in Example 1 is concentrated at 1 nm or even smaller, while the pore size of the hard carbon material in Comparative Example 1 is more distributed around 4 nm, and there is no obvious concentrated pore size distribution area, which fully confirms the pore-forming effect of freeze-drying on the hard carbon precursor, and more closed pores are formed in the subsequent high-temperature carbonization process.
[0074] like Figure 5 As shown in the figure, the SAXS spectrum and fitting results of the hard carbon material prepared in Example 1, it can be seen that the material -1 There is an obvious peak near it, indicating that the closed pore radius increases and the closed pore content is high. The average pore size obtained by the fitting result is 2.056nm, which is consistent with Figure 4 The results of the pore size distribution diagrams are inconsistent. This is because N 2 This is due to the fact that no abundant closed pores could be detected in the adsorption-desorption test.
[0075] like Figure 6 As shown, this is the first charge and discharge curve of the hard carbon material prepared in Example 1. It can be seen that the first cycle charge and discharge capacity of the hard carbon material is 350.69 mAh / g and 382.32 mAh / g respectively, and the Coulomb efficiency is about 91.73%. The irreversible capacity loss in the first cycle (8.27%) is due to the decomposition of the electrolyte and the formation of a solid electrolyte film on the surface of the hard carbon material.
[0076] Table 1 shows the test results of the charge and discharge performance of the batteries prepared by the examples and comparative examples. It can be seen that the batteries prepared by the method of the present invention have excellent electrochemical properties, among which Example 1 is the best, with a first charge specific capacity of 350.69 mAh / g and a first-week coulombic efficiency of up to 91.73%. Compared with Comparative Example 1, Example 1 has a higher charge specific capacity, and the first-week coulombic efficiency is also significantly improved. This is because the large number of open pores created by freeze drying for the hard carbon precursor are clustered to form closed pores during the subsequent high-temperature carbonization process, thereby providing abundant sodium storage sites. Similarly, compared with Comparative Example 2, Example 1 has a better first-week coulombic efficiency. This is due to the addition of sodium ion accelerated desolvation technology, which successfully solves the problem that the electrolyte desolvation rate at the interface between the long-handled almond shell-based hard carbon material and the electrolyte is too slow, resulting in too many solvated structures participating in the reaction as a whole, resulting in excessive irreversible loss of sodium ions.
[0077] Table 1 Test results of charge and discharge performance of batteries prepared in Examples and Comparative Examples
[0078]
[0079]
Claims
1. A method for preparing a sodium ion button half-cell, characterized in that: Follow the steps below to implement it: S1, washing the long-pedunculate almond shell, drying it, crushing it and passing it through a 100-mesh sieve to obtain long-pedunculate almond shell powder; S2, using excess hydrochloric acid to remove impurity ions in the long-handled almond shell powder obtained in step S1, filtering out the hydrochloric acid, and then washing and drying the powder; S3, breaking the powder obtained in step S2 into cells, freezing it, and then freeze-drying it; S4, carbonizing the powder obtained in step S3 under Ar atmosphere to obtain a long-handled almond shell-based hard carbon material; S5, using the hard carbon material obtained in step S4 as a negative electrode material to prepare a negative electrode sheet; S6, using the negative electrode sheet obtained in step S5 as the negative electrode, the sodium sheet as the positive electrode, and a glass fiber separator to assemble a sodium ion button half-cell; S7, subjecting the button-type half-cell assembled in step S6 to a sodium ion accelerated desolvation treatment to obtain a sodium ion button-type half-cell.
2. The method for preparing a sodium ion button half-cell according to claim 1, characterized in that: Step S2 is specifically as follows: The long-handled almond shell powder obtained in step S1 is immersed in excess hydrochloric acid and stirred for 4 to 6 hours to remove impurity ions therein. After filtering out the hydrochloric acid, the powder is ultrasonically washed with deionized water, and then dried by blast drying and vacuum drying.
3. The method for preparing a sodium ion button half-cell according to claim 2, characterized in that: The specific drying process is: forced air drying at 60-80°C for 12-15h, and then vacuum drying at 90-100°C for 12-15h.
4. The method for preparing a sodium ion button half-cell according to claim 1, characterized in that: Step S3 is specifically as follows: Deionized water having a mass of 10 to 15 times the mass of the powder is added to the long-handled almond shell powder obtained in step S2, and the mixture is stirred for 1 to 2 hours, and then the cells are broken for 2 to 3 hours, and then the mixture is frozen for 24 to 48 hours, and then freeze-dried for 36 to 48 hours.
5. The method for preparing a sodium ion button half-cell according to claim 1, characterized in that: In step S4, the specific carbonization process is: heating to 1200-1600°C at a rate of 1-5°C / min and then keeping the temperature for 3 hours.
6. The method for preparing a sodium ion button half-cell according to claim 1, characterized in that: Step S5 is specifically as follows: A conductive agent and a binder are added to the long-handled almond shell-based hard carbon material obtained in step S4 and mixed to obtain an active slurry, the active slurry is coated on a current collector, and vacuum dried at 60°C for 24 hours to obtain a negative electrode sheet; wherein the conductive agent is conductive carbon black, the binder is formed by dissolving polyvinylidene fluoride in N-methyl-2-pyrrolidone, the mass ratio of the long-handled almond shell-based hard carbon, the conductive carbon black and the polyvinylidene fluoride is 8:1:1, and the current collector is copper foil.
7. The method for preparing a sodium ion button half-cell according to claim 1, characterized in that: In step S7, the specific steps of the sodium ion accelerated desolvation treatment are: maintaining a constant temperature of 60-80° C. in a vacuum drying oven for 7-8 days.
8. A sodium ion button half-cell, characterized in that: The compound is prepared by the preparation method described in any one of claims 1 to 7.
Citation Information
Cited By
Method for preparing porous carbon through photo-thermal driven biomass conversion minute level
CN121894644A
